Scontri tra culture e scontri nelle culture. Italia e Spagna tra Quattro e Cinquecento - Cappelli, Guido M. (Cuadernos de Filología Clásica. Estudios Latinos, 2004)
The Emergency of Spain on the italian political scene between 15th. aid 16th. Century modified how the italian scholarship perceived spanish culture and civilization. Throughout the works of Oiovanni Pontano, Tristano Caracciolo, and Antonio Galateo, one can observe the trouble for the increasing power and domination of Spain in Europe